Rhetoric and Emotion Save Science: Lessons from Student Eco-Activists - Jesse Priest (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
This essay is a qualitative study of the experience of undergraduate students learning how to teach issues of sustainability to their campus communities through an innovative outreach program at a large northeastern research university, while at the same time learning to navigate complex emotional labor required by their outreach and activist work. While most previous work on science writing and rhetoric focuses on disciplinary, publishing, or genre practices, I examine the holistic student experience by placing outreach, writing, and the classroom in conversation with each other, illuminating how discourses can cross institutional and contextual borders. Additionally, while most previous work involving student engagement has focused on its positive and rewarding aspects, I examine how tension and critical moments can also be productive learning experiences for students, suggesting ways in which teachers might recognize the often-invisible aspects of students’ emotional labor that impact their learning experiences. I consider ways in which moments of tension represent productive opportunities for education, wholly separate from traditional notions of success in learning. I propose a re-orientation towards how we view engagement and success in educational contexts to allow for and even welcome moments of frustration as valid and productive representations of emotional labor
Keywords: Education; Emotional Labor; Eco-Activism; Science Writing; Sustainability